ChatGPT, a brand-new tool to strengthen timeless competencies - Michalon, Barthélémy; Camacho-Zuñiga, Claudia (Frontiers in Education, 2023)
This work contributes to the growing body of research on how Artificial Intelligence (AI) can be used in higher education settings to enhance learning experiences and outcomes. In November 2022, the public release of ChatGPT, an AI natural language model, was a groundbreaking point in education and in many sectors of human life. We describe how ChatGPT was integrated in an undergraduate course for an International Relations program in a private Mexican university. Under an action research methodology, the purpose was to have the students use the tool for certain Future Studies methods. They were evaluated on their ability to explain and to implement these methods step by step. After six learning activities, the outcomes evidenced that the students not only learned how to use the new AI tool and deepen their understanding of prospective methods, but also strengthened three soft or transversal competencies: communication, critical thinking, and logical and methodological reasoning. These results are promising in the framework of Skills for Industry 4.0 and Education for Sustainable Development; even more, they demonstrate how ChatGPT created an opportunity for the students to strengthen, and for the professor to assess, time-tested competencies. This is a call-to action for faculty and educational institutions to incorporate AI in their instructional design, not only to prepare our graduates for professional environments where they will collaborate with these technologies but also to enhance the quality and relevance of higher education in the digital age.